2016
DOI: 10.11114/jets.v5i1.1947
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Classroom Pre-Service Teachers’ State of Personal Innovativeness

Abstract: Today, in every passing moment, a new piece of information is acquired and the accumulation of this information leads to social and technological developments. Therefore, today, individuals are expected to rapidly adjust to innovations. As such, individuals should be open to innovations and willing to adopt innovations; that is, they need to be innovative. In this regard, most of the responsibility for training innovative individuals within formal education should be assumed by classroom teachers as they are w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
(5 reference statements)
2
4
0
Order By: Relevance
“…Studies on innovation in the literature indicate that preservice teachers are generally in the early majority category (Adigüzel, 2012;Çuhadar et al, 2013;Erdoğan & Güneş, 2013;Kert & Tekdal, 2012;Korucu & Olpak, 2015;Mazman Akar, 2019;Özgür, 2013;Suer & Kinay, 2019;Yorulmaz et al, 2017). In the research conducted in the current study, it was determined that the innovativeness categories of the preservice teachers were similar to that reported in the literature prior to the application.…”
Section: Development Of Preservice Teachers' Personal Innovativeness ...supporting
confidence: 56%
“…Studies on innovation in the literature indicate that preservice teachers are generally in the early majority category (Adigüzel, 2012;Çuhadar et al, 2013;Erdoğan & Güneş, 2013;Kert & Tekdal, 2012;Korucu & Olpak, 2015;Mazman Akar, 2019;Özgür, 2013;Suer & Kinay, 2019;Yorulmaz et al, 2017). In the research conducted in the current study, it was determined that the innovativeness categories of the preservice teachers were similar to that reported in the literature prior to the application.…”
Section: Development Of Preservice Teachers' Personal Innovativeness ...supporting
confidence: 56%
“…(3 studies), school demographics (3 studies), teaching experience (3 studies) teacher eligibility (3 studies) and student level (2 studies). Although gender recorded the highest frequency of study, three of these studies were conducted in the same location in Turkey (Aslan & Kesik, 2018;Doç & Yapıcı, 2016;Yorulmaz et al, 2016). All six factors in this demographic category were studied in relation to teachers' innovative behaviour directly without using other factors as mediators and moderators.…”
Section: Demographic Factormentioning
confidence: 99%
“…al. ( 2016 ), who also demonstrated that personal innovativeness is higher among female pre-service teachers in Turkey than male peers. Our results contradict, to some extent, Adachi and Hisada’s ( 2016 ) study, which posits that, in general, women have less inclination towards intrapreneurship than men.…”
Section: Discussionmentioning
confidence: 97%